2014
DOI: 10.1155/2014/185676
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity ofArtemisia amygdalinaDecne in Streptozotocin Induced Diabetic Rats

Abstract: Artemisia species have been extensively used for the management of diabetes in folklore medicine. The current study was designed to investigate the antidiabetic and antihyperlipidemic effects of Artemisia amygdalina. Petroleum ether, ethyl acetate, methanol, and hydroethanolic extracts of Artemisia amygdalina were tested for their antidiabetic potentials in diabetic rats. The effect of extracts was observed by checking the biochemical, physiological, and histopathological parameters in diabetic rats. The hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 33 publications
6
31
0
Order By: Relevance
“…Based on our results, treatment of the STZ-induced diabetic rats separately with A. turanica extract and metformin significantly decreased blood glucose level as compared to the untreated diabetic rats. In the same context, Ghazanfar et al (2014) reported significant decrease in blood level of glucose in STZ-induced diabetic animals receiving Artemisia amygdalina extract [ 20 ]. The antidiabetic activities of Artemisia judaica , Artemisia annua and Artemisia herba-alba have also been reported [ 21 – 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, treatment of the STZ-induced diabetic rats separately with A. turanica extract and metformin significantly decreased blood glucose level as compared to the untreated diabetic rats. In the same context, Ghazanfar et al (2014) reported significant decrease in blood level of glucose in STZ-induced diabetic animals receiving Artemisia amygdalina extract [ 20 ]. The antidiabetic activities of Artemisia judaica , Artemisia annua and Artemisia herba-alba have also been reported [ 21 – 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their Hypoglycemic effect was comparable with that of the usual hypoglycemic drugs repaglinide, insulin, metformin and glibenclamide. [ 7 15 19 20 ] However, as can be seen from the study of some of those species of Artemisia, such as Artemisia herba-alba have a greater potency in decreasing the serum glucose level and animals treated with this plant showed only mild visible undesirable clinical symptoms whereas the synthetic oral hypoglycemic agents can produce serious side effects. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…These drugs also have certain adverse effects such as causing hypoglycemia at higher doses, liver problems, lactic acidosis and diarrhea. [ 7 ] Apart from these available therapeutic options, many herbal medicines have been recommended for the treatment of diabetes. Traditional herbal medicines are used throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples were collected from the tail vein of the overnight (12-15h) fasted rats and blood glucose level was determined on 0th, 5th, 10th and 15th day along with body weight and body temperature. On the 15th day, all the animals were sacrificed and evaluated for the biochemical parameters, histopathology of the pancreas tissue [12,13]. On the 15 th day of treatment, blood was collected from the animals and centrifuged at 4000 rpm for 5 min to separate the serum.…”
Section: Experimental Designmentioning
confidence: 99%